A Qualitative Approach to Understand Migrant Worker’s Psycho-Social Problems in Malaysia - Khan, Abdul Mujeeb; Hashim, Abdul Talib Mohmedd; Yousuf, Muhammad; Assaiqeli, Aladdin (International Journal of Psychosocial Rehabilitation, 2020)
Malaysia is one of the major migrant workers’ receiving countries in Southeast Asia. The migrants from various countries like Cambodia, Indonesia, the Philippines, Myanmar, and South Asian countries come to Malaysia for job opportunities. According to Malaysia's immigration department’s statistics, a total of 1.99 million foreign workers in Malaysia were registered under the Temporary Visiting Work Permit as by August 31, 2019. The majority of workers are semi and low skilled, mainly working in manufacturing, construction, services sector, plantation, etc. The research objective is to examine the migrant worker’s psychological issues, intercultural issues, ethnocentrism and overall issues related to adaptation in a foreign country. The data will be obtained by using the qualitative method− in-depth interviews with 30 participants using the non-probability sampling technique from three countries, namely, Bangladesh, Nepal and Pakistan. Expectantly, the results of this study will give enormous insight to understand migrant worker’s issues which can ultimately help in reviewing migrant worker’s sending countries’ policies as well as Malaysian policies to improve chances of migrant worker’s psychological wellbeing.